ADAM17 As Inducer of Male Germ Cell Apoptosis (International Journal of Medical and Surgical Sciences, 2015)
Apoptosis during mammalian spermatogenesis is important to control sperm output and to eliminate damaged unwanted cells. A deregulation in apoptosis rate has deleterious consequences and leads to low sperm production. Apoptosis in spermatogenesis has been widely studied, but the mechanism by which it is induced under physiological or pathological conditions has not been clarified. We have recently identified the metalloprotease ADAM17 (TACE) as a putative physiological inducer of germ cell apoptosis. ADAM17 is widely distributed enzyme in many tissues, its main function is to shed (release) its substrates, which leads to the activation of different signaling pathways according to the cellular context. However, in spermatogenesis, ADAM17 is involved in the control or induction of germ cell apoptosis, this seems to be unique and may reflect the complexity of spermatogenesis. In this review I will focus on the published evidence that show how this enzyme involved in the control of germ cell apoptosis during physiological condition and in different insults such as heat stress, DNA damaging agent or endocrine disruptors.
Keywords: ADAM17; Apoptosis; male germ cell